44.2k views
1 vote
Given f(x)
=
4x + 1
3
solve for F-1(3). (5 points)

User DreamWave
by
5.6k points

1 Answer

7 votes

Answer:

Explanation:

First we need to find inverse function of f(x) which is written in a form of (f(x))^(-1)

That means that we are actually looking for function f(y) and we need to solve this equation for "y"

y=(4x + 1)/3

3y = 4x + 1

4x = 3y - 1

x = (3y - 1) / 4

f(y) = (3y - 1)/4

Now we simply put the value of 3 instead of y and find the answer:

f(y=3) = (3*3-1)/4 = 2

Answer is 2

User Lucas Watson
by
6.2k points